A generative framework for creative learning: A tool for planning creative-collaborative tasks in the classroom - Truman, Sylvia (Border Crossing, 2011)
In this paper a generative framework for creativity is presented which extends upon Wallas’s model of creativity (1926), social learning theories and creativity theories. The framework offered here presents a distillation of learning and crea-tivity theory drawing upon salient roots of both creativity and learning theories in the 21st century. The generative framework can be instantiated for use as a learning support tool to assist with the design of classroom and / or other crea-tive learning experiences. Creativity theories are discussed in relation to their appropriateness of the framework. An explanation of the framework is present-ed and an example instantiation provided. The development of the generative framework has been influenced by psychological accounts of creativity and socio-constructivist accounts of learning. The framework presented here has a number of implications for creativity theory as well as teaching and learning practice.